Optimalisasi Sistem Informasi Desa (SID) untuk Transparansi Anggaran dan Pelayanan Publik di Setda Kabupaten Banjar: Pengabdian - Khairullah Anshari; Devia Hetty Hernany; Amelia Puspita; Muhammad Amin Hafi; Rani Inayah; Muhammad Hafi; Masrifah; Aji Rahadian (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to improve the capacity of village officials to utilize the Village Information System (SID) as an instrument for budget transparency and strengthening public services. The program was implemented in collaboration with the Banjar Regency Regional Secretariat through a series of technical training sessions, implementation assistance, needs analysis, and evaluation of SID use in several pilot villages. The results of the program demonstrated a significant increase in village officials' understanding of budget features, data publication, and digital-based village administration service processing. Furthermore, there was a shift in work patterns toward more open, participatory, and accountable village governance. This program emphasized that optimizing SID requires synergy between regulations, human resource capacity, and local government commitment.